2015
DOI: 10.1111/jam.12936
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and antibiotic resistance profiles of Pseudomonads from a hospital wastewater treatment plant

Abstract: The presence of MDR bacteria from treated effluents alerts for the need to improve these systems to avoid the spreading of resistance genes in aquatic ecosystems. This has special relevance in Brazil, where a significant portion of the population has no access to treated water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…Resistance was also noted to have emerged in some environmental lineages against various antibiotics, for instance, ertapenem, cefoxitin, amikacin, and amoxicillin-clavulanic acid in sewage water isolates (Additional file 2: Figure S3), which presumably arises in response to antibiotics in environmental wastewater, as reported previously [42, 43]. Several studies have shown the presence of highly antibiotic-resistant bacteria and resistance genes in sewage released into aquatic environments [42, 4446]. In line with these findings, our results suggest that the release of untreated hospital sewage may play a role in the environmental emergence and spread of multiresistant pathogenic bacteria, and that wastewater (including hospital waste) warrants treatment to eliminate these organisms prior to release.…”
Section: Discussionsupporting
confidence: 53%
“…Resistance was also noted to have emerged in some environmental lineages against various antibiotics, for instance, ertapenem, cefoxitin, amikacin, and amoxicillin-clavulanic acid in sewage water isolates (Additional file 2: Figure S3), which presumably arises in response to antibiotics in environmental wastewater, as reported previously [42, 43]. Several studies have shown the presence of highly antibiotic-resistant bacteria and resistance genes in sewage released into aquatic environments [42, 4446]. In line with these findings, our results suggest that the release of untreated hospital sewage may play a role in the environmental emergence and spread of multiresistant pathogenic bacteria, and that wastewater (including hospital waste) warrants treatment to eliminate these organisms prior to release.…”
Section: Discussionsupporting
confidence: 53%
“…The role of hospitals in the environmental release of antibiotic-resistant bacteria and ARGs has been demonstrated and has become a growing concern for public health [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Hospital WWTPs can harbour antibiotic-resistant bacteria and ARGs [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of culture-based techniques, some consensus is emerging around E. coli as a highly suitable target (Blaak et al, 2015b;Liang et al, 2015), although many other potentially useful bacterial targets, such as Klebsiella spp. (Berendonk et al, 2015), fecal enterococci (Berendonk et al, 2015), and bacteria that grow in aquatic/soil environments such as Pseudomonas aeruginosa (Santoro et al, 2015) or various Aeromonads exist. However, E. coli is a practical choice given that it is already the most widely monitored target as an indicator of fecal pollution and thus methodologies are already standardized and infrastructure is more likely to be in place to implement monitoring campaigns based on E. coli (Matheu et al, 2017).…”
Section: Detection Methods For Antibiotic Resistance Monitoring Targetsmentioning
confidence: 99%